2016
DOI: 10.1155/2016/5706432
|View full text |Cite
|
Sign up to set email alerts
|

Natural Polymer of Iraqi Apricot Tree Gum as a Novel Corrosion Inhibitor for Mild Steel in 1 M HCl Solution

Abstract: Corrosion inhibition of mild steel in 1 M hydrochloric acid using Iraqi apricot tree gum Arabic as natural polymer was studied. The weight loss method was used to predict the efficiency of the inhibitor on corrosion of mild steel in a temperature range of 17–40°C. The FTIR result of natural polymer revealed that the C=O and O-H groups were found in the structure of the natural polymer. The results of weight loss method showed that the inhibition efficiency (I%) increased with the increase in both the natural p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…They were suspended in deionized water through GA surfactant, which was chosen because it can form more stable solutions especially at high temperatures [ 39 ]. GA is an organic inhibitor of complex structure [ 44 ] that can reduce corrosion attack by being physically or chemically adsorbed on the surface of the metal [ 44 , 45 ]. GA molecules can be adsorbed into the surfaces through their functional groups, namely hydroxyl (–OH) and carboxyl (–COOH) ones [ 46 ].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…They were suspended in deionized water through GA surfactant, which was chosen because it can form more stable solutions especially at high temperatures [ 39 ]. GA is an organic inhibitor of complex structure [ 44 ] that can reduce corrosion attack by being physically or chemically adsorbed on the surface of the metal [ 44 , 45 ]. GA molecules can be adsorbed into the surfaces through their functional groups, namely hydroxyl (–OH) and carboxyl (–COOH) ones [ 46 ].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The surface coverage, θ , was fitted, with R. mangle L. bark-extract concentration, ρ , to the Langmuir adsorption isotherm [76, 9092]:T1ρθ=1Kads+ρFrom this fitting in (11), estimation of the K ads , the equilibrium constant for Langmuir absorption-desorption process, was used for modelling R L , the separation factor, and Δ G ads °, the Gibbs free energy for the adsorption model, respectively fromT17RL=11+KadsCR0ΔGads=log55.5Kads2.303RTBy the value of the R L , it is possible to indicate that R. mangle L. bark-extract adsorption on the studied steel-rebar is irreversible for R L = 0, or favourable for 0 < R L < 1, or linear for R L = 1, or unfavourable for R L > 1. Similarly, the value of Δ G ads ° would be indicative of prevalent physisorption for Δ G ads ° around –20 kJ/mol or prevalent chemisorption for Δ G ads ° around –40 kJ/mol.…”
Section: Methodsmentioning
confidence: 99%
“…There are some researches that studied natural inhibitor substances as corrosion inhibitors for iron and steel materials in acidic media (Abdallah, 2004; El‐Etre, 2003; El‐Etre & Abdallah, 2000; Oguzie, 2005). Alwaan and Mahdi (2016) evaluated the effect of PAGE concentration and different temperatures (17–40°C) on the ability of this gum for corrosion inhibition of mild steel. It was found that with addition of PAGE to the acid solution (1 M HCl), the weight loss of the mild steel decreased and due to the presence of carbonyl and hydroxyl groups in PAGE composition, PAGE can adhere on the iron metal.…”
Section: Food and Pharmaceutical Applicationsmentioning
confidence: 99%
“…Since the functional and physicochemical characteristics of the hydrocolloids are mainly dependent on their chemical composition as well as structural properties (Sherahi et al., 2017), it is necessary to determine the chemical composition and structural properties of the new source of hydrocolloids. Various studies have been conducted to characterize Prunus family gum exudates (PAGE) and evaluate its physicochemical, structural, and functional properties (Al‐idee et al., 2020; Alwaan & Mahdi, 2016; Azam Khan et al., 2012; Babken et al., 2018; Bouaziz et al., 2015; Chichoyan, 2015; Chichoyan & Shaboyan, 2016; Ding et al., 2019; Ergin et al., 2018; Fathi, Mohebbi, & Koocheki, 2016a, 2016b; Fathi et al., 2017; Hamdani et al., 2017, 2018; Hashemi & Raeisi, 2018; Islam et al., 2019; Jamila et al., 2020; Khorsha et al., 2016; Kora, 2018; Licá et al., 2018; Lluveras‐Tenorio et al., 2012; Molaei & Jahanbin, 2018; Najafi et al., 2020; Rahim et al., 2018; Shamsara et al., 2015, 2017; Shi et al., 2019; Stephen & Shirley, 1986; Theophil Anand et al., 2019; Wei, Zhang, He, et al., 2019; Wei, Zhang, Zhang, et al., 2019; Zhang et al., 2020). We tried to present a compressive review on the documents on PAGE to explore its potential application in food, textile, cosmetic, and pharmaceutical systems.…”
Section: Introductionmentioning
confidence: 99%